Помогите решить уравнения: -3*(2,1х-4)-4,2=1,2*(-5х+0,5) 6,4*(2-3х)=6*(0,8х-1)+6,8 4*(3-х)-11=7*(2х-5) 0,9*(4х-2)=0,5*(3х-4)+4,4
Помогите решить уравнения:
-3*(2,1х-4)-4,2=1,2*(-5х+0,5)
6,4*(2-3х)=6*(0,8х-1)+6,8
4*(3-х)-11=7*(2х-5)
0,9*(4х-2)=0,5*(3х-4)+4,4
Ответ(ы) на вопрос:
-3*(2,1х-4)-4,2=1,2*(-5х+0,5)
-6,3х+12-4,2=-6х+0,6
-6,3х+6х=0,6-12+4,2
-0,3х=-7,2
Х=-7,2/-0,3
Х=24
6,4*(2-3х)=6*(0,8х-1)+6,8
12,8-19,2х=4,8х-6+6,8
-19,2х-4,8х=6,8-6-12,8
-24х=-12
Х=-12/-24
Х=0,5
Не нашли ответ?
Похожие вопросы